2016
DOI: 10.1111/epi.13450
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early life status epilepticus on ultrasonic vocalizations in mice

Abstract: Summary Objective Infant crying is a series of innate vocal patterns intended to elicit the attention of adult caregivers for fulfillment of specific needs, such as pain, hunger, or hypostimulation. It is one of the earliest forms of observable communication. In neonatal rodents, this behavior has recently been investigated as a potential early behavioral marker of neural deficits in neurodevelopmental disorders. However, few studies have examined the effects of seizures on vocalization behavior during the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
2
8
1
Order By: Relevance
“…Our results are different from previous studies that described a pattern of decreased call duration in both rat and mouse pups [15,16,18]. In the Lopez-Meraz et al, 2014 study, they found a suppression in the number of USVs in PD14 rats.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results are different from previous studies that described a pattern of decreased call duration in both rat and mouse pups [15,16,18]. In the Lopez-Meraz et al, 2014 study, they found a suppression in the number of USVs in PD14 rats.…”
Section: Discussioncontrasting
confidence: 99%
“…In the Lopez-Meraz et al, 2014 study, they found a suppression in the number of USVs in PD14 rats. A similar suppression of USVs was reported in the other two studies, which were conducted in mice [15,16]. One key difference between these studies and the current study is that they used the chemoconvulsant pilocarpine or kainic acid to induce status epilepticus on a single day.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations